Using Propensity to Succeed Modeling to Increase Utilization and Adherence in a Nurse HealthLine Telephone Triage Program. Issue 3 (July 2016) - Navratil-Strawn, Jessica L.; Hawkins, Kevin; Hartley, Stephen K.; Wells, Timothy S.; Ozminkowski, Ronald J.; Migliori, Richard J.; Yeh, Charlotte S.
Abstract : Propensity to succeed modeling was used to identify characteristics associated with higher utilization of a telephone triage program and adherence to nurse recommendations among callers. Characteristics significantly associated with calling the telephone triage service and engaging in triage services were being female and having an elevated health risk score. Callers most likely to adhere to nurse recommendations were younger than 85 years of age, had called on a weekday, and had received a recommendation to seek care at an emergency department or a doctor's office visit. Additional analyses suggest the propensity to succeed modeling is stable and valid.